Communicative Effect Taxonomy Analysis in Students Oral Production - Moriyanti, Moriyanti; Ismail, Nyak Mutia (Universitas Serambi Mekkah, 2023)
This study aims at finding out Communicative Effect Taxonomy in students oral productionspecifically on local and global errors. This study is qualitative in nature involving 16 first grader at SMPN 2 Muara Tiga, Pidie. The instrument used was analytical table which was constructed based on the theory of Communicative Effect Taxonomy. The data collection was carried out by following the steps of: sample collection, errors identification, error description, error clarification, and error assessment. The data analysis was conducted afterward in line with the following phases: identification of errors, classification of errors, evaluation, and conclusion. It is found that local erros were produced more compared to global errors (52 local errors and 45 global errors) in the students speaking performance. Regarding the implication, the result from this study can enhance the development of more accurate and dependable evaluation tools for measuring students' oral communication skills by establishing a classification system for communicative impacts. Consequently, this can exert a substantial influence on educational policies and practices.